(untitled) (Fiep Bulletin - online, 2024)
Introduction: Shoulder pain is the second dominant complaint in osteoarticular specialty outpatient clinics, which can harm 15 to 25% of the population, with the occurrence increasing with advancing age. In turn, acupuncture is a technique of traditional Chinese medicine that aims to cure through the insertion of needles into specific points on the body’s energy channels, which we call meridians. Objective: This research aims to evaluate the benefits of acupuncture in the treatment of chronic pain in the shoulder joint. Methods: For this, four patients with chronic shoulder pain will be recruited to undergo acupuncture treatment, using common and specific acupuncture points for each patient, according to the eastern diagnosis of pulse and tongue. Finally, the results of the treatment will be compared. Results: Complaints and pain in the shoulder joint were eliminated after completing the pre-established sessions. Conclusion: It was possible to observe, through the data obtained in this research, that acupuncture is an effective technique for treating and eliminating shoulder pain. Overall, it contributes to improving the quality of life.